Use of Whole-Genome Sequencing to Estimate the Contribution of Immune Evasion and Waning Immunity on Decreasing COVID-19 Vaccine Effectiveness. (21st November 2022) - Lind, Margaret L; Copin, Richard; McCarthy, Shane; Coppi, Andreas; Warner, Fred; Ferguson, David; Duckwall, Chelsea; Borg, Ryan; Muenker, M Catherine; Overton, John; Hamon, Sara; Zhou, Anbo; et al.
Abstract: Background: The impact variant-specific immune evasion and waning protection have on declining coronavirus disease 2019 (COVID-19) vaccine effectiveness (VE) remains unclear. Using whole-genome sequencing (WGS), we examined the contribution these factors had on the decline that followed the introduction of the Delta variant. Furthermore, we evaluated calendar-period–based classification as a WGS alternative. Methods: We conducted a test-negative case-control study among people tested for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) between 1 April and 24 August 2021. Variants were classified using WGS and calendar period. Results: We included 2029 cases (positive, sequenced samples) and 343 727 controls (negative tests). VE 14–89 days after second dose was significantly higher against Alpha (84.4%; 95% confidence interval [CI], 75.6%–90.0%) than Delta infection (68.9%; 95% CI, 58.0%–77.1%). The odds of Delta infection were significantly higher 90–149 than 14–89 days after second dose ( P value = .003). Calendar-period–classified VE estimates approximated WGS-classified estimates; however, calendar-period–based classification was subject to misclassification (35% Alpha, 4% Delta). Conclusions: Both waning protection and variant-specific immune evasion contributed to the lower effectiveness. While calendar-period–classified VE estimates mirrored WGS-classified estimates, our analysis highlights the need for WGS when variants are cocirculating and misclassification is likely. Abstract : Using whole genome sequencing (WGS), we provide direct evidence of waning vaccine effectiveness and variant-specific immune evasion during the Delta wave. Effectiveness estimates against calendar-period–classified infections approximated estimates against WGS-classified infections; however, calendar-period classification was associated with variant misclassification.